Novel Small Molecule Glucagon-Like Peptide-1 Receptor Agonist S6 Stimulates Insulin Secretion From Rat Islets - Yang, Xiaohua; Zhang, Min; Lu, Zhihong; Zhi, Linping; Xue, Huan; Liu, Tao; Liu, Mengmeng; Cui, Lijuan; Liu, Zhihong; He, Peifeng; Liu, Yunfeng; Zhang, Yi (Frontiers in Pharmacology, 2021)
Glucagon-like peptide-1 receptor (GLP-1R) agonist-based therapeutics for type 2 diabetes mellitus have attracted worldwide attention. However, there are challenges in the development of small molecule GLP-1R agonists owing to the complexity of ligand recognition and signal induction mechanisms. Here, we attained S6 using virtual screening and fluorescent imaging plate reader (FLIPR)-based calcium assays. The purpose of this study was to identify and characterize S6, a novel small molecule GLP-1R agonist. Data from cellular thermal shift assay (CETSA) and Bio-Layer Interferometry (BLI) indicated that S6 could bind potently with GLP-1R. Radioimmunoassay data showed that S6 potentiated insulin secretion in a glucose-dependent manner and the insulinotropic effect was mediated by GLP-1R. Calcium imaging techniques suggested that S6 elevated the intracellular calcium concentration ([Ca2+]i) by activating GLP-1R. In patch-clamp experiments, we demonstrated that S6 inhibited voltage-dependent K+ (Kv) channels in a GLP-1R-dependent fashion. Besides, S6 significantly prolonged action potential duration but had no effect on voltage-dependent Ca2+ channels. In summary, these findings indicate that S6 stimulates glucose-dependent insulin secretion mainly by acting on GLP-1R, inhibiting Kv channels, increasing [Ca2+]i. This study will provide direction for the screening and development of novel small-molecule agents targeting GLP-1R in the future.